The Students’ Speaking Skill Analaysis on Local Wisdom- Based Topics (A Study at the First Year Grade of Mathematics Department of Unswagati) - Devi Siti Afiah (Lembaga Penelitian (The Institute of Research) Universitas Swadaya Gunung Jati, 2017)
The goals of this research are (1) to know what students’ responses toward WH question tehnique; (2) to know whether the WH Question can improve students’ math in English. This research used the descriptive qualitative method. The writer described and analyzed the students’ mistakes in speaking skill using local materials. The research was carried out at the first year students of math department in 2016/2017 academic year. It was strated from September 2016 to January 2017. The population was the first semester students of math department in academic year of 2016/2017. The number of population were 21 students. The results of this research were (1) the tudents gave good responses toward the WH Questions learning, and (2) the WH questions improved the Math students’ ability in learning English. Keywords: Speaking, Local-wisdom, WH-questions